2017
DOI: 10.1038/s41598-017-08795-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental enrichment upon ethanol-induced conditioned place preference and pre-frontal BDNF levels in adolescent and adult mice

Abstract: Environmental enrichment (EE) provides a non-pharmacological tool to alter drug-induced reward, yet its effects on ethanol-induced reward remain controversial. We analyzed adolescent vs. adult (mice) differences in the influence of EE on ethanol-induced conditioned place preference (CPP). The effects of these treatments on brain-derived neurotrophic factor (BDNF) levels in the prefrontal cortex were examined in a separate group of animals. Ethanol-induced CPP was found in adults, and it was similar in EE and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 64 publications
(82 reference statements)
1
9
0
1
Order By: Relevance
“…Several studies have reported that EE may enhance ethanol seeking and intake (7,8,32). EE heightened ethanol-induced conditioned place preference in adolescent mice but not in adult mice (11). When EE was applied on the same postnatal days as in the present study, it heightened ethanol intake in male rats but not in female rats (9).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Several studies have reported that EE may enhance ethanol seeking and intake (7,8,32). EE heightened ethanol-induced conditioned place preference in adolescent mice but not in adult mice (11). When EE was applied on the same postnatal days as in the present study, it heightened ethanol intake in male rats but not in female rats (9).…”
Section: Discussionsupporting
confidence: 45%
“…Rodents that were reared under EE conditions exhibited reductions of cocaine-(4) and ethanol-induced conditioned place preference (5) and reductions of drug intake (6). Nonetheless, some studies have reported that EE may enhance drug selfadministration (7)(8)(9) or the effects of ethanol (10,11) by increasing risk-taking or novelty-seeking behavior (9). We also measured anxiety-like behavior in the light-dark box (LDB) (12).…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the effects of EE upon alcohol vulnerability in the first weeks of the two-bottle-choice paradigm is not univocal since we observed mixed effects in the control offspring. In this regard, EE has been reported to promote the formation of conditioned place preference to alcohol in adolescent mice, likely recruiting the oxytocin signaling (Pautassi et al, 2017 ; Rae et al, 2018 ). However, the postweaning exposure to EE substantially rescued the increased vulnerability induced by perinatal alcohol exposure in p-CAD and p-IAD offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the environmental-enrichment (EE), experimental paradigm consisting of housing conditions that include novelty, social interaction and exercise, enhances sensory, cognitive, and motor stimulation, which, in turn, translates into increased neuroplasticity in brain regions critical for emotional regulation, cognitive functions and reward sensitivity (Bayat et al, 2015 ; Crofton et al, 2015 ; Morera-Herreras et al, 2019 ). However, conflicting evidence is reported when the effect of EE was evaluated toward motivational effects of drugs of abuse, including alcohol (Nithianantharajah and Hannan, 2006 ; Solinas et al, 2009 ; Pautassi et al, 2017 ; Rae et al, 2018 ). Thus, while it is critical to identify maternal alcohol consumption as a primary target to prevent fetal consequences, we investigated whether EE during adolescence could prevent or mitigate the effects of perinatal alcohol exposure on behavioral readouts of cognitive function and alcohol vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF regulates neural cell survival and differentiation as well as several functions related to neural plasticity such as learning and memory (157). A recent study found that BDNF levels in the pre-frontal cortex were significantly lower in the group of mice treated with ethanol in comparison to the control group (158). The study concluded that the impairment in learning and memory observed in mice exposed to ethanol was associated to changes in BDNF levels.…”
Section: Trophic Supportmentioning
confidence: 99%